Metabolic depression: a historical perspective - Withers, P.; Cooper, Christine (2010)
An extended period of inactivity and reduced metabolic rate of many animals and plants, as well as unicellular organisms, has long been recognized by natural historians, e.g., Aristotle and Pliny. Biologists have studied this phenomenon since the 1550s (Gessner) and 1700s (Van Leeuwenhoek, Buffon). The period of inactivity can be less than a day, a few consecutive days or weeks, an entire season, or even many years. It can involve very different physiological states in response to a variety of environmental stimuli, such as extreme temperatures or unavailability of food or water. These periods of inactivity have been described and classified according to the group of organisms in question, extent and duration of the metabolic depression, ambient and body temperatures, state of body water (frozen or hyperosmotic), or availability of oxygen. Cryptobiosis, or “hidden life,” is an extreme form of inactivity, with often complete cessation of metabolism. It was first described in the 1700s, was further characterized in the 1800s, and in the 1900s physiological studies delineated the extent of metabolic depression. Molecular mechanisms for cryptobiosis have been sought since the late 1900s. Cryptobiosis includes three physiological states, anhydrobiosis (desiccation), osmobiosis (high osmotic concentration), and cryobiosis (freezing), where metabolic depression is associated with an altered physical state of cell water and often involves accumulation of compatible solutes, and one physiological state, anoxybiosis (anoxia), where metabolic depression occurs at the normal cellular hydration state. Dormancy (torpor) is a less extreme form of inactivity, associated with a moderate reduction in metabolic rate (hypometabolism). Although first described by Aristotle and Pliny, studies in the 1900s delineated the basic physiological changes that accompany dormancy. Dormancy allows avoidance of unfavorable short- or long-term climatic conditions and conservation of energy and water. Hibernation is long-term multiday torpor during winter, whereas aestivation is dormancy during summer. In ectotherms, the metabolic depression that accompanies dormancy is intrinsic, with metabolic rate declining to about 10 to 20% of resting metabolic rate at the same body temperature. The molecular mechanisms for intrinsic metabolic depression are poorly understood. In endotherms, torpor involves a fundamental physiological change in body temperature regulation that markedly reduces metabolic rate and water loss, often to <10% of the normothermic resting metabolic rate at the same ambient temperature. Most of this reduction in metabolic rate reflects the decreased setpoint for thermoregulation resulting in reduced metabolic heat production and a Q10 effect; there may be some intrinsic molecular-based metabolic depression in some hibernators. Dormancy allows species to exploit ephemeral environments and colonise habitats that would otherwise be unsuitable for growth or survival at certain times of the year. There are costs to dormancy, but for many species, the energetic and hygric advantages outweigh these costs.